PENEGAKAN HUKUM LINGKUNGAN ADMINISTRATIF DALAM UNDANG-UNDANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Kartono Kartono (Faculty of Law, Universitas Jenderal Soedirman, 2009)
General population growth has increased with increasing environmental risk and high consumption of chemical-based products. This condition requires the need for environmental laws tougher life than before. Therefore, on 8 September 2009 and then, the House has passed the bill Protection and Management of the Environment into law. One of the new things in this legislation is the creation of a new type of license, i.e environmental permit. The aim is to strengthen the supervisory authority of the Ministry of Environment protection and environment management. However, the law does not regulate the supervision institutions, so that the authority is structurally integrated into the existing institutions. With such authority, the government should reform the laws and regulations which can substantially support the performance monitoring, both regarding the amount of oversight, supervision and frequency standards of supervision. But on the other aspects of supervision as a form of preventive law enforcement is also facing challenges related inconsitency legal terminology in its formulation. It is necessary for creativity in its application of law enforcement so that law enforcement process does not face constraints in the implementation means. Kata Kunci : pengawasan, izin lingkungan, penegakan hukum